Pelatihan Autocad Untuk Peningkatan Kompetensi Siswa Kelas X Jurusan Teknik Konstruksi dan Perumahan SMKN 1 Rengat Barat Kabupaten Indragiri Hulu - Lisa Trisnawati; Erny Erny; Hazanawati Hazanawati; Nafriandi Nafriandi; Sri Guntur; Julinaldi Julinaldi (Fakultas Teknik Universitas Cenderawasih, 2023)
The purpose of this community service activity is to train and guide the skills of West Rengat 1 Vocational School students in an effort to increase competence in the field of drawing with the AutoCAD program because one of the competencies that vocational students must have, especially those majoring in construction and housing engineering, is drawing using the AutoCAD application. The methods used in this training activity include presentation, demonstration, practice and evaluation. The results of the evaluation of this activity were obtained from the assignments given to each student. The instructor checks the images that have been made by all participants including the size and shape of the images. From the initial observation to the final evaluation process, it was found that there was an increase in the knowledge and skills of the students, who initially did not have the ability to draw using AutoCAD, but after the training was given the participants were able to apply the program. The evaluation results showed that as many as 64% of the participants were able to do the drawing assignments that had been given. Keywords: AutoCAD, Competency Improvement, SMK Students.